Aeromonas hydrophila Ssp1: A secretory serine protease that disrupts tight junction integrity and is essential for host infection. Issue 127 (August 2022) - Feng, Chen; Liu, Xiaofeng; Hu, Niewen; Tang, Yiyang; Feng, Mengzhe; Zhou, Zejun
Abstract: Aeromonas hydrophila is a Gram-negative bacterial pathogen with a broad host range, including fish and humans. In this study, we examined the function of a secretory serine protease (named Ssp1) identified in pathogenic A . hydrophila CCL1. Ssp1 possesses a trypsin-like serine protease domain and contains two conserved PDZ domains. Recombinant Ssp1 protein (rSsp1) treatment increased intestinal permeability by downregulating and redistributing tight junction protein Occludin in intestinal Caco-2 cells in vitro . Western blot demonstrated that rSsp1 treatment in Caco-2 cells resulted in marked increases in the expressions of myosin light chain kinase (MLCK) and phosphorylated myosin light chain (p-MLC). For virulence analysis, an isogenic CCL1 mutant Δ Ssp1 was created. Δ Ssp1 bears an in-frame deletion of the Ssp1 gene. A live infection study in crucian carps showed that, compared to CCL1, Δ Ssp1 infection exhibited increased Occludin expression, reduced intestinal permeability and tissue dissemination capacity, and attenuated overall virulence in vivo . However, Δ Ssp1 showed no differences in the biofilm formation, swimming motility, and resistance to environmental stress. These lost virulence capacities of Δ Ssp1 were restored by complementation with the Ssp1 gene. Global transcriptome analysis and quantitative real-time RT-PCR showed that compared to CCL1 infection, Δ Ssp1 promoted the expressions of antimicrobial molecules ( MUC2, LEAP-2, Hepcidin-1, and IL-22 ). Finally, CCL1 infection caused significant dysbiosis of the gut microbiota, including increased Vibrio and Deefgea compared to Δ Ssp1 infected fish. Taken together, these results indicate that Ssp1 is essential for the virulence of A . hydrophila and is required for the perturbation of intestinal tight junction barrier. Highlights: A virulent Aeromonas hydrophila CCL1 was isolated from the diseased crucian carp. rSsp1 increased intestinal permeability in intestinal Caco-2 cells in vitro. Δ Ssp1 infection reduced intestinal permeability and attenuated overall virulence in vivo.